Prediksi Utang Luar Negeri Indonesia dengan Menganalisis Cadangan Devisa terhadap Nilai Ekspor Indonesia Periode Tahun 2003 - 2016 - R Rudi Alhempi; Dodi Irawan Siregar (Jurnal Ekonomi KIAT, 2019)
Indonesia's foreign debt has increased dramatically in the last decade both government and private debt, and has taken up a portion of Indonesia's state budget (APBN). The amount of principal payments and debt interest is almost double the Indonesian development budget. For this reason, an effort is needed to pay it off, that is, every country needs foreign exchange reserves as a means of foreign payment, export activities will increase the country's foreign exchange reserves, which in turn can strengthen economic fundamentals. One of the government's efforts to obtain foreign exchange from abroad is by making loans to other countries (foreign debt) and exporting the results of natural resources and non-natural resources abroad. From the results of this foreign exchange can be used to increase state development funds. This study uses multiple linear regression analysis. The results of this study indicate that: Multiple linear regression analysis can be used to predict Indonesia's foreign debt by analyzing foreign exchange reserves against Indonesia's export value; There is a large (significant) partial effect between foreign exchange reserves and foreign debt; There is no significant (partial) significant effect between the value of exports on foreign debt.